Proceedings of the Events and Stories in the News Workshop 2017
DOI: 10.18653/v1/w17-2711
|View full text |Cite
|
Sign up to set email alerts
|

The Event StoryLine Corpus: A New Benchmark for Causal and Temporal Relation Extraction

Abstract: This paper reports on the Event StoryLine Corpus (ESC) v0.9, a new benchmark dataset for the temporal and causal relation detection. By developing this dataset, we also introduce a new task, the StoryLine Extraction from news data, which aims at extracting and classifying events relevant for stories, from across news documents spread in time and clustered around a single seminal event or topic. In addition to describing the dataset, we also report on three baselines systems whose results show the complexity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
59
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(75 citation statements)
references
References 17 publications
0
59
0
Order By: Relevance
“…The resulting dataset contains 2,470 sentences, of which 244 are causal. Event StoryLine (EventSL): In this dataset (Caselli and Vossen, 2017), we detected causal sentences by examining the CAUSES and CAUSED BY attributes in the PLOT LINK tags, again following Li and Mao (2019). Again, we discarded causal relationships between entities from different sentences.…”
Section: Datasetsmentioning
confidence: 99%
“…The resulting dataset contains 2,470 sentences, of which 244 are causal. Event StoryLine (EventSL): In this dataset (Caselli and Vossen, 2017), we detected causal sentences by examining the CAUSES and CAUSED BY attributes in the PLOT LINK tags, again following Li and Mao (2019). Again, we discarded causal relationships between entities from different sentences.…”
Section: Datasetsmentioning
confidence: 99%
“…The EventStoryLine corpus is the largest dataset for causal relation identification till now with comprehensive event causal relations annotated, both intra-sentence and cross-sentence, which presents unique challenges for causal relation identification. Caselli and Vossen (2017) showed that only 117 annotated causal relations in this dataset are indicated by explicit causal cue phrases while the others are implicit. We conduct experiments on the EventStoryLine dataset.…”
Section: Related Workmentioning
confidence: 92%
“…Our approach innovates on modeling other aspects of document-level causal structures, especially heavy involvements of main events in causal relations, that facilitate resolving multiple causal relations. Table 1 shows the statistics of the corpus EventStoryLine v0.9 1 (Caselli and Vossen, 2017 Causal relations annotated in EventStoryLine are between two event mentions. Different causal relations are annotated in EventStoryLine, called "rising action" and "falling action", which indicate the directions of causal relations and intuitively correspond to "precondition" and "consequence" relations.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Of various efforts in guided generation [Ammanabrolu et al, 2019;Tang et al, 2019;Clark et al, 2018;Hu et al, 2019b], Sentential Causal Resource # CE Pairs TCR [Ning et al, 2018] 172 SemEval-2007Task4 [Girju et al, 2007 220 Causal-TimeBank [Mirza et al, 2014] 318 CaTeRS [Mostafazadeh et al, 2016] 488 EventCausalityData [Do et al, 2011] 580 RED [O'Gorman et al, 2016] 1,147 SemEval2010 Task8 [Hendrickx et al, 2009] 1,331 BECauSE 2.0 [Dunietz et al, 2017b] 1,803 EventStoryLine [Caselli and Vossen, 2017] 5,519 PDTB 2.0 [Prasad et al, 2008] 8,042 Altlex [Hidey and McKeown, 2016] 9,190 PDTB 3.0 [Webber et al, 2019] 13 K DisSent [Nie et al, 2019] 167 K CausalBank (Ours) 314 M…”
Section: Related Workmentioning
confidence: 99%